Exploration of the Path of Mental Health Education for Left-behind Children in Rural Areas under the Coordinated Mechanism (Journal of research in medical and health sciences, 2026)
This study focuses on mental health education for rural left-behind children, analyzing typical psychological issues such as emotional deficits caused by parent-child separation, behavioral deviations resulting from excessive grandparents' indulgence, and inappropriate behaviors stemming from estranged parent-child relationships. Given the challenges in rural mental health education—including teacher shortages, marginalized curricula, and difficulties in interdisciplinary integration—the study proposes establishing a comprehensive intervention framework characterized by "government leadership, school-centered initiatives, family participation, and social collaboration." Government departments should dismantle household registration barriers to ensure school enrollment rights for migrant children while increasing funding for mental health services. Schools should implement dynamic psychological record management systems and develop personalized activity plans for targeted interventions. Parents are encouraged to enhance emotional communication and refine educational approaches. Society should coordinate resources to build a comprehensive support system. Only through multi-stakeholder collaboration mechanisms can the mental health status of rural left-behind children be significantly improved, creating a more favorable environment for their growth.
Keywords: Rural left-Behind children; Mental health education; Collaborative mechanism; Educational pathway